How the COVID‐19 pandemic has changed our lives: A study of psychological correlates across 59 countries. Issue 3 (31st October 2020) - Alzueta, Elisabet; Perrin, Paul; Baker, Fiona C.; Caffarra, Sendy; Ramos‐Usuga, Daniela; Yuksel, Dilara; Arango‐Lasprilla, Juan Carlos
Abstract: Objective: This study examined the impact of the COVID‐19 pandemic and subsequent social restrictions or quarantines on the mental health of the global adult population. Method: A sample of 6, 882 individuals ( Mage = 42.30; 78.8% female) from 59 countries completed an online survey asking about several pandemic‐related changes in life and psychological status. Results: Of these participants, 25.4% and 19.5% reported moderate‐to‐severe depression (DASS‐21) and anxiety symptoms (GAD‐7), respectively. Demographic characteristics (e.g. higher‐income country), COVID‐19 exposure (e.g., having had unconfirmed COVID‐19 symptoms), government‐imposed quarantine level, and COVID‐19‐based life changes (e.g., having a hard time transitioning to working from home; increase in verbal arguments or conflict with other adult in home) explained 17.9% of the variance in depression and 21.5% in anxiety symptoms. Conclusions: In addition to posing a high risk to physical health, the COVID‐19 pandemic has robustly affected global mental health, so it is essential to ensure that mental health services reach individuals showing pandemic‐related depression and anxiety symptoms.